UTILIZATION OF MANTIS SHRIMP RESOURCES (Harpiosquilla raphidea) IN LABUHANBATU WATERS, NORTH SUMATRA PROVINCE - Siregar, Irham Huspa Khasahatan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Mantis shrimp (Harpiosquilla raphidea) can be found in the waters of Labuhanbatu, North Sumatra Province. The significant economic value and fishing effort of this shrimp species are believed to affect the decline in population numbers in the Labuhanbatu aquatic ecosystem, which has the potential to threaten the sustainability of its natural habitat. This study aimed to analyze the resource utilization of mantis shrimp in Labuhanbatu waters. The research methodology used was secondary data analysis. The research was conducted from November 2024 to April 2025, specifically in the waters of Labuhanbatu, North Sumatra Province. The dataset analyzed includes time series data from 2017 to 2024, including information on mantis shrimp catches and the number of fishing trips obtained from the Labuhanbatu Regency Marine and Fisheries Service. Data analysis was carried out using the Gordon-Schaefer bioeconomic model, along with calculations of utilization rates and effort rates. The results of the resource utilization analysis showed that mantis shrimp in Labuhanbatu have been overexploited. In catch rate optimization and cost reduction, scenarios that produce maximum economic yield (MEY) show higher profitability than scenarios based on maximum sustainable yield (MSY). This highlights the unsustainability of open-access mantis shrimp fishing practices in Labuhanbatu waters and the potential for mantis shrimp resource depletion. Furthermore, the utilization rate estimated at 93% indicates overexploitation, where the exploitation rate exceeds the MSY threshold. In addition, the effort rate reached 91%, indicating that the production capacity is almost at the maximum limit.